Intermediate maturing soybean produce multiple benefits at 1:2 maize: soybean planting density - Simbine, M.G.; Baijukya, Frederick P.; Onwonga, R.N. (Canadian Center of Science and Education, 2018)
A study was conducted to identify the most suitable intercropping arrangement in smallholder farms in Western Kenya. Biomass and N (nitrogen)-accumulation, N2 fixation and grain yield of maize and soybeans grown as intercrops at three planting densities were assessed. The study was conducted in four seasons. Three soybean varieties, Namsoy 4m, SC Squire and TGx1987-18F, were used in the experiment. Maize: soybean planting densities 1:1 (D1), 1:2 (D2), 1:3 (D3) as well as sole soybean (SS) and sole maize (SM) were tested. Higher biomass, N-accumulation, and N-fixed in the order 3.8 Mg ha-1, 260 kg ha-1 and 161 kg ha-1 respectively, were recorded in D3 with long maturing variety TGx1987-18F. Conversely, higher soybean grain yield < 2.4 Mg ha-1 was achieved by intermediate maturing SC Squire in D3. The highest maize yield in the intercrop was obtained in D1. N balance calculations indicated that planting TGx1987-18F resulted in an addition of 6 to 67 kg N ha-1, while SC Squire and Namsoy 4 m removed 3 to 89 kg N ha-1 when soybean grain was removed from the field. The differences in N balances between the intercrops depended on the N-fixed and the amount of N in harvested soybean and maize grain. Greater land equivalent ratio < 1.75 were obtained with SC Squire and Namsoy 4m in D2. We concluded that intermediate maturing soybean have multiple benefits for farmers in Western Kenya at 1:2 maize: soybean planting density provided that the practice is accompanied with good soil and crop management practices.